Commitment in cases of trust and distrust - Tallant, Jonathan (Philosophy Documentation Center, 2017)
There is a well-developed literature on trust. Distrust, on the other hand, has gathered far less attention in the philosophical literature (though there is a burgeoning business literature on the topic). A recent exception to that trend in the philosophical literature is Hawley (2014, 2015) who develops a unified account of both trust and distrust. My aim in this paper is to present arguments against her account of trust and distrust, though then to also suggest a patch.